The Analysis Of Determining The Selling Price With Variabel Costing And Activity Based Costing Method In CV. Madani Digital Printing - Aa Kartiwa (SINTESA, 2023)
Every company always has a target to make a profit. It takes the right methods and calculations to obtain these profits. The purpose of this study is to find out how the role in determining the selling price using the variable costing method and the ABC method on CV. Madani Digital Printing. After using the calculation with the determination of variable cost of goods, the expected profit can be achieved while the selling price per set is higher. The selling price per sofa set using the ABC method is lower than the variable method. CV. Madani Digital Printing has not set a precise and accurate selling price. The company's calculation method is not correct, CV Madani Digital Printing has not done it well in setting the selling price, there are marketing costs and administrative and general costs that have not been taken into account. By determining the selling price using the variable costing method, including marketing and administrative and general costs, it is proven that the expected profit can be achieved. Using the ABC method can be useful for CV Madani Digital Printing to achieve maximum profit as expected, continuous evaluation must be carried out considering that changes in material costs are very dynamic, so that in setting selling prices more precisely and competing with competitors